Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1105/tpc.109.072579
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Control of Trichome Distribution by MicroRNA156-TargetedSPLGenes inArabidopsis thaliana   

Abstract: The production and distribution of plant trichomes is temporally and spatially regulated. After entering into the flowering stage, Arabidopsis thaliana plants have progressively reduced numbers of trichomes on the inflorescence stem, and the floral organs are nearly glabrous. We show here that SQUAMOSA PROMOTER BINDING PROTEIN LIKE (SPL) genes, which define an endogenous flowering pathway and are targeted by microRNA 156 (miR156), temporally control the trichome distribution during flowering. Plants overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
277
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(293 citation statements)
references
References 75 publications
5
277
1
3
Order By: Relevance
“…7A), which represent three subgroups of miRNA-regulated SPL genes (Guo et al, 2008). These genes were also chosen because they contribute to the regulation of sepal trichome number in Arabidopsis (Shikata et al, 2009;Yu et al, 2010;Wei et al, 2012). We found that ChSPL3 expression increased stepwise from vegetative to early inflorescence to anthesis stages of development, while ChSPL9 expression increased from early inflorescence to anthesis stages (Fig.…”
Section: Petal Number Regulation By Endogenous Signalsmentioning
confidence: 89%
See 1 more Smart Citation
“…7A), which represent three subgroups of miRNA-regulated SPL genes (Guo et al, 2008). These genes were also chosen because they contribute to the regulation of sepal trichome number in Arabidopsis (Shikata et al, 2009;Yu et al, 2010;Wei et al, 2012). We found that ChSPL3 expression increased stepwise from vegetative to early inflorescence to anthesis stages of development, while ChSPL9 expression increased from early inflorescence to anthesis stages (Fig.…”
Section: Petal Number Regulation By Endogenous Signalsmentioning
confidence: 89%
“…This variation is strongly influenced by plant ageing, such that petal number per flower declines as a plant ages. Another phenotype that shows this temporal trend is the declining number of trichomes on the abaxial side of sepals as a plant ages (Shikata et al, 2009;Yu et al, 2010), and both of these age-dependent traits share a common genetic basis in C. hirsuta . Therefore, common QTL affect both petal number and sepal trichome number and act in an age-dependent manner.…”
mentioning
confidence: 99%
“…20,21 These plantspecific SPB-box proteins are known to influence a large array of developmental processes in Arabidopsis, such as promoting the juvenile-to-adult phase transition by activating miR172, inducing flowering via activating LEAFY and the MADS box genes, inhibiting trichome initiation on floral organs through activating TCL1, as well as concertedly controlling male fertility. [21][22][23][24] Recently, the miR156/157-targeted SPLs have been shown to affect metabolic fluxes through the branched flavonoid biosynthetic pathway. 4 Dihydroflavonols serve as common precursors of flavonols and anthocyanins and can be oxidized either by FLS to form flavonols or reduced by DFR to produce leucoanthocyanidins in the first dedicated step for anthocyanin biosynthesis (Fig.…”
Section: Spl9 Negatively Reguates Anthocyanin Accumulation Via Destabmentioning
confidence: 99%
“…Consistent with our previous research [4], the mRNAs of SPL9 were cleaved within the complementary region of GhmiR156. The target of miR156, SPL9, has been reported to play critical roles in the temporal control of trichome distribution in Arabidopsis thaliana [25].…”
Section: Target Prediction Validation and Gene Ontology Analysismentioning
confidence: 99%